Gonadotropin-releasing hormone (GnRH) - its approaches to improve reproduction in fish - Fatin Nabilah Sahadan,; Annie Christianus,; Md Yasin Ina-Salwany,; Fadhil-Syukri Ismail,; Roshani Othman,; Zarirah Zulperi, (Universiti Kebangsaan Malaysia, 2022)
This review briefly highlights previous studies on the gonadotropin-releasing hormone (GnRH) and its approaches to improving fish reproduction in the aquaculture industry. Reproductive system dysfunction of the captive fish is the main problem that has to be treated depending on the compatibility of fish species. This problem is caused by the non-synchronized maturation of female and male broodstock, and the low quality of broodstock. As shown in previous studies, induced breeding with exogenous treatment from specialized hormones could be one of the best cures for this issue. Hormonal treatments have been used by farmers to overcome the reproductive system dysfunctions in establishing captive wild or hatchery-based breeding. Although the imitation in its natural condition has been set up, for broodstock to spawn naturally problems still occur, hence the need for hormonal therapy. This review aims to deliver the results and contributions of an established artificial hormone, gonadotropin-releasing hormone analogue (GnRHa), to treat fish reproductive system dysfunction, to improve the qualities of eggs, seedlings, and broodstock, mainly to help fish farmers and can be used in the aquaculture industry to improve the reproduction of cultured fishes for sustainable aquaculture production to achieve the market demand and consumption.